PANDORE: an environmental box for ITk integration tests. (1st April 2022) - Costanza, F.; Allemandou, N.G.; Chabanne, E.; Cornudet, E.; Delebecque, P.; Gaglione, R.; Jeremie, A.; Leveque, J.; Massol, N.; Mievre, I.; Prevost, O.; Vilalte, S.
Abstract: PANDORE is the environmental box that is going to be used for the quality control of loaded local supports of the ATLAS ITk Pixel Outer Barrel at LAPP (Annecy, France). First PANDORE, its interlock system, diphasic CO2 cooling station, and data acquisition system are described. Subsequently, the results of the qualification tests are shown. Given the complexity of the ITk Pixel Outer Barrel system, several loading sites are going to be needed. By documenting the state-of-the-art of PANDORE, this note aims to help the wide ITk Pixel community in the discussion for standardizing the quality control procedure and equipment of the loaded local supports.